The entrepreneurial modeling of women is based on the entrepreneurial value chain with a sustainable social development approach in the province of Gulistan - Nafiseh Varkianipor; Majid Ashrafi (تحقیقات کاربردی علوم جغرافیایی)
The promotion of Entrepreneurship is the need of the community and the entrepreneursial development factors that are essential is the. Of the employment of women in Iran. Pursuit of opportunities beyond resources to create values in an article on the Entrepreneurship of the Entrepreneurship chain and sustainable social development. The elements of value chain were identified and prioritized according to experts in the second part of the paper to measure the relationship between the development of women's entrepreneurship and sustaninable social development through correlation research and strucrural equation modeling. We then discussed the results and the model entrepreneurial development model was developed based on the entrprenrurial value chain with a sustainable social development approach. This model contributes to the formulation of women's entrepreneurial activity and tacilitates the srengths and weaknesses and facilitates. Finally the presentation of the model and the link between the development of women's entrepreneurship of entrepreneurship value chain and sustainable social development were obtained.